Comparison of the 7th edition of the International Union Against Cancer and the Chinese 2008 staging systems for nasopharyngeal carcinoma and recommendations for future updates. Issue Volume 1:Issues 1(2017) (12th January 2017) - Liang, Zhongguo; Lei, Hao; Chen, Zetan; Li, Ling; Qu, Song; Su, Fang; Zhao, Wei; Pei, Su; Pan, Xinbin; Zhu, Xiaodong
Abstract: Objective: To compare the 7th edition of the International Union Against Cancer (UICC) and the Chinese 2008 staging systems for nasopharyngeal carcinoma (NPC), and to provide evidence for further updates to these NPC staging systems. Methods: A retrospective analysis was carried out on 767 patients with newly diagnosed, pathologically confirmed non‐metastatic NPC who were treated with intensity‐modulated radiotherapy between 2006 and 2012. The prognostic value of the T category, N category, and clinical stage for the main survival outcomes of overall survival (OS), local relapse‐free survival and distant metastasis‐free survival were compared between the two staging systems. The Kaplan–Meier method was used to calculate survival rates, the log–rank test was used to compare survival rates, and the Cox model was used for the multivariate prognostic analysis. Results: The T categories of the Chinese 2008 staging system had a significantly better prognostic value for OS and local relapse‐free survival than those of the 7th edition of the UICC staging system. The N categories of both staging systems had a comparable prognostic value for OS and distant metastasis‐free survival. The clinical stages of the 7th edition of the UICC staging system had a significantly better prognostic value for OS than those of the Chinese 2008 staging system. Based on these analyses, the T categories, N categories, and clinical stages of our proposed staging system had a significantly better prognostic value compared with the original staging system. Conclusions: The 7th edition of the UICC staging system and the Chinese 2008 staging system for NPC each has its own advantages with respect to prognostic prediction. The recommended staging system proposed in the present study could contribute to the next update of the current staging systems for NPC.